Preparation and application of high-performance dual-phase solid electrolyte membrane
By adding lithium salt and ceramic particles in the preparation process of polymer solid electrolyte membrane and controlling phase conversion and drying conditions, a high-performance solid electrolyte membrane with a biphasic structure was prepared, which solved the low ionic conductivity of the existing membrane and Mechanical performance issues achieve efficient ion conduction and structural stability of electrolytes.
Patent Information
- Application Number
- CN202411410662.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-18
AI Technical Summary
The existing polymer solid electrolyte membrane has low ionic conductivity and improper concentration of conductive agent will lead to a decrease in mechanical properties, making it difficult to control the phase separation process.
By dissolving PVDF-HFP in an organic solvent, adding lithium salt and ceramic particles, controlling the temperature and stirring time, adding deionized water for phase conversion, and finally drying and curing in the mold to form a film, a high-performance solid state with a biphasic structure was prepared. Electrolyte membrane.
The high ion conductivity, enhanced mechanical strength and good mechanical properties of the solid electrolyte membrane are achieved, the structural stability of the electrolyte is ensured, and excellent cycling performance is shown in lithium metal batteries.
Smart Images

Figure CN119481232A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to the preparation and application of a high-performance dual-phase solid electrolyte membrane. Background Art
[0002] With the widespread use of lithium batteries, battery safety has become increasingly important. Solid electrolytes provide a safer alternative to traditional flammable electrolytes and can remain stable even under extreme conditions. The preparation and processing costs of polymer solid electrolytes are relatively low compared to other types of battery materials, which helps reduce the overall cost of batteries and promotes their commercial application.
[0003] Among polymer solid electrolytes, polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) has excellent chemical stability, high mechanical strength and flexibility, and good film-forming properties, which enables it to reduce the chemical reaction between the electrolyte and the electrode material and maintain the integrity of the structure. The PVDF-HFP film has stable electrochemical properties within the electrochemical window range and can form a uniform film through solution processing technology, which is conducive to large-scale production.
[0004] However, there are still many problems in the development of this type of membrane. The ionic conductivity of PVDF-HFP itself is relatively low and needs to be improved by adding ionic conductive agents such as lithium salts. However, improper use of the concentration of the conductive agent will lead to a decrease in the mechanical properties of the electrolyte membrane. During the preparation process, the phase separation behavior of PVDF-HFP and the conductive agent and other additives has a great influence on the microstructure and porosity of the electrolyte membrane. Therefore, it is a challenge to control the phase separation process, including the selection of solvents, the temperature of phase separation, the drying film forming process, etc., to obtain an ideal pore structure. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation and application of a high-performance dual-phase solid electrolyte membrane, which is specifically achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a high-performance dual-phase solid electrolyte membrane, comprising the following steps:
[0007] (1) dissolving PVDF-HFP in an organic solvent, adding lithium salt, and stirring at a constant temperature to prepare a polymer solution;
[0008] (2) adding ceramic particles to the polymer solution, stirring and mixing at a maintained temperature to obtain a mixed solution in a reddish uniformly dispersed state;
[0009] (3) adding deionized water to the mixed solution, maintaining the temperature and stirring to obtain a mixed solution after phase conversion;
[0010] (4) Pour the phase-converted mixed solution into a mold and dry and solidify it into a film to obtain a solid electrolyte membrane.
[0011] Wherein, the stirring temperature maintained in steps (1) to (3) is 40-60°C, for example, 43°C, 45°C, 48°C, 50°C, 52°C, 55°C, 58°C or 60°C.
[0012] Furthermore, the average molecular weight of the PVDF-HFP is 350,000-455,000, preferably 370,000-430,000, further preferably 380,000-415,000, and more preferably 395,000-405,000.
[0013] Furthermore, the mass percentage of PVDF-HFP in the polymer solution is 9.9-15%, for example, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14% or 14.5%.
[0014] Furthermore, the mass percentage of lithium salt in the polymer solution is 0.1%-15%, for example 0.5%, 1.5%, 2%, 3%, 5%, 7%, 9%, 10%, 12%, 13%, 14% or 15%.
[0015] Furthermore, the mass percentage of the organic solvent in the polymer solution is 70-90%, for example, 72%, 75%, 78%, 80%, 82%, 85%, 88% or 90%.
[0016] Furthermore, the lithium salt is one or more of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) or lithium perchlorate (LiClO4).
[0017] Furthermore, the organic solvent is one of acetone, acetonitrile and tetrahydrofuran.
[0018] Furthermore, the mass percentage of ceramic particles in the mixed solution is 15%-25%, for example, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%.
[0019] Furthermore, the ceramic particles are any one of LLZTO (lithium lanthanum zirconium tantalum oxide), LLZO (lithium lanthanum zirconium oxide), LLTO (lithium lanthanum titanium oxide) or LATP (lithium aluminum titanium phosphate).
[0020] Furthermore, in step (3), the mass ratio of the deionized water to the mixed solution is 1-2:10.
[0021] Furthermore, in the step (4), the temperature for drying and curing the film is 30-85° C., and the time is 12-20 h, for example, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h.
[0022] Among them, the drying and curing film-forming method can be selected according to actual needs, such as vacuum drying.
[0023] Among them, the purpose of drying and solidifying the film is to evaporate the organic solvent. The internal pore size and microstructure of the solid electrolyte membrane are controlled by controlling the temperature and time (i.e., rate) of the drying film. The internal pore size and microstructure of the solid electrolyte membrane are the main factors affecting the electrochemical properties of the solid electrolyte.
[0024] In the process of preparing the solid electrolyte membrane, the present invention forms a good phase structure in the electrolyte membrane through the volatilization and evaporation of the organic solvent. The volatile organic solvent is selected and the organic solvent can be evaporated by combining the temperature control drying means. For example, the volatilization temperature of acetone is 20-30° C. and the boiling point (evaporation temperature) is 56° C. At the same time, considering that the volatilization of the solvent at too high a temperature will form a small pore membrane due to the excessively fast evaporation rate of the solvent molecules, which is not conducive to ensuring the performance of the electrolyte, the drying temperature can be controlled according to the volatility and evaporation temperature of the selected organic solvent.
[0025] The type of solvent, the mass fraction of the polymer solution, and the type and mass fraction of the additive (lithium salt) are all key factors in controlling the membrane microstructure. Therefore, only under the joint action of the type of solvent, the mass fraction of the polymer solution, the evaporation temperature and time can the prepared solid electrolyte membrane form a specific porous structure. In addition, deionized water also plays a role as a solvent in the phase exchange process.
[0026] Furthermore, the solid electrolyte membrane has a thickness of 350-800 μm, for example, 350 μm, 400 μm, 420 μm, 450 μm, 470 μm, 500 μm, 520 μm, 550 μm, 580 μm, 600 μm, 630 μm, 650 μm, 700 μm, 750 μm or 800 μm.
[0027] In a second aspect, the present invention provides a high-performance dual-phase solid electrolyte membrane prepared by the above method.
[0028] In a third aspect, the present invention provides a lithium metal battery comprising the above-mentioned high-performance dual-phase solid electrolyte membrane. Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention prepares a solid electrolyte membrane with a dual-phase structure by selecting and controlling the solid electrolyte raw materials, proportions and film-forming conditions, wherein the dispersed phase is honeycomb-shaped and rich in ion-conductive groups, thereby improving the ion conduction of the electrolyte and increasing the specific surface area and mechanical strength of the electrolyte; the continuous phase is the main enrichment area of the PVDF-HFP polymer, which can provide flexibility for the electrolyte; the dual-phase structure is alternately distributed on the entire solid electrolyte membrane, which brings good mechanical properties to the electrolyte and ensures the structural stability of the electrolyte; the composite solid electrolyte prepared by the present invention has high ionic conductivity, and the ionic conductivity can reach 10 at room temperature. -3 The high conductivity of the electrolyte has shown excellent development potential in the research and development of solid-state batteries. The ternary lithium battery system assembled by the dual-phase solid electrolyte membrane of the present invention has good cycle performance under multiple charge and discharge rates, and the battery also has stable operation performance.
[0030] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of a solid electrolyte membrane with a dual-phase structure prepared in Example 3 of the present invention;
[0032] Figure 2 This is a local magnified scanning electron microscope image of two phases of the solid electrolyte membrane prepared in Example 3 of the present invention;
[0033] Figure 3 The electrochemical impedance spectra of the solid electrolyte membranes prepared in Examples 1-4 of the present invention;
[0034] Figure 4 The cycle specific capacity curves measured for the solid-state batteries assembled in Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the implementation scheme of the present application will be described in detail below in conjunction with specific examples. The technical terms and scientific terms used in the present invention have the meanings generally understood by ordinary technicians in the technical field to which the present invention belongs, without other definitions. Without departing from the concept of the present invention, those skilled in the art may make various improvements and changes to the specific implementation methods of the present invention specification, which all belong to the protection scope of the present invention.
[0036] The technical solution of the present invention will be further described below in conjunction with embodiments.
[0037] Example 1
[0038] Step 1: dissolve 5 g of vinylidene fluoride-hexafluoropropylene copolymer in 40 ml of acetone (purity greater than 97%) to prepare a polymer solution, then add 0.574 g of LiTFSI to the polymer solution, stir evenly at 50° C. for 2 h to obtain a polymer solution;
[0039] Step 2: Add 1 g of LLZTO ceramic powder to the polymer solution, disperse the powder evenly by ultrasound, and stir in a water bath at 50° C. for 2 h to obtain a mixed solution in a reddish evenly dispersed state;
[0040] Step 3: Add 5 ml of deionized water to the mixed solution and continue stirring at 50° C. for 8 h to allow the solute and solvent to fully undergo phase conversion to obtain a mixed solution after phase conversion.
[0041] Step 4: Finally, pour the mixed solution after phase conversion into a glass culture dish and cast it into a 500 μm thick film. Dry and solidify it in a vacuum drying oven. Control the evaporation temperature to 30°C and the time to 18 hours to obtain a solid electrolyte membrane with uniform composition and a dual-phase structure.
[0042] The prepared solid electrolyte membrane was used to assemble an NCM811|solid electrolyte membrane|Li solid-state battery.
[0043] Example 2
[0044] Step 1: dissolve 5 g of vinylidene fluoride-hexafluoropropylene copolymer in 45 ml of acetone (purity greater than 97%) to prepare a polymer solution, then add 0.574 g of LiTFSI to the polymer solution, stir evenly at 50° C. for 2 h to obtain a polymer solution;
[0045] Step 2: Add 1 g of LLZTO ceramic powder to the polymer solution, disperse the powder evenly by ultrasound, and stir evenly in a water bath at 50° C. for 2 h to obtain a mixed solution in a reddish evenly dispersed state;
[0046] Step 3: Add 6 ml of deionized water to the mixed solution and continue stirring at 50° C. for 8 h to allow the solute and solvent to fully undergo phase conversion to obtain a mixed solution after phase conversion.
[0047] Step 4: Finally, pour the mixed solution after phase conversion into a glass culture dish and cast it into a 500 μm thick film. Dry and solidify it in a vacuum drying oven. Control the evaporation temperature to 30°C and the time to 18 hours to obtain a solid electrolyte membrane with uniform composition and a dual-phase structure.
[0048] The prepared solid electrolyte membrane was used to assemble an NCM811|solid electrolyte membrane|Li solid-state battery.
[0049] Example 3
[0050] Step 1: dissolve 5 g of vinylidene fluoride-hexafluoropropylene copolymer in 40 ml of acetone (purity greater than 97%) to prepare a polymer solution, then add 0.574 g of LiTFSI to the polymer solution, stir evenly at 50° C. for 2 h to obtain a polymer solution;
[0051] Step 2: Add 1 g of LLZTO ceramic powder to the polymer solution, disperse the powder evenly by ultrasound, and stir evenly in a water bath at 50° C. for 2 h to obtain a mixed solution in a reddish evenly dispersed state;
[0052] Step 3: Add 5 ml of deionized water to the mixed solution and continue stirring at 50° C. for 8 h to allow the solute and solvent to fully undergo phase conversion to obtain a mixed solution after phase conversion.
[0053] Step 4: Finally, pour the mixed solution after phase conversion into a glass culture dish and cast it into a 500 μm thick film. Dry and solidify it in a vacuum drying oven. Control the evaporation temperature to 40°C and the time to 12 hours to obtain a solid electrolyte membrane with uniform composition and a dual-phase structure.
[0054] The prepared solid electrolyte membrane was used to assemble an NCM811|solid electrolyte membrane|Li solid-state battery.
[0055] Example 4
[0056] Step 1: dissolve 5 g of vinylidene fluoride-hexafluoropropylene copolymer in 50 ml of acetone (purity greater than 97%) to prepare a polymer solution, then add 0.574 g of LiTFSI to the polymer solution, stir evenly at 50° C. for 2 h to obtain a polymer solution;
[0057] Step 2: Add 1 g of LLZTO ceramic powder to the polymer solution, disperse the powder evenly by ultrasound, and stir evenly in a water bath at 50° C. for 2 h to obtain a mixed solution in a reddish evenly dispersed state;
[0058] Step 3: Add 5 ml of deionized water to the mixed solution and continue stirring at 50° C. for 8 h to allow the solute and solvent to fully undergo phase conversion to obtain a mixed solution after phase conversion.
[0059] Step 4: Finally, pour the mixed solution after phase conversion into a glass culture dish and cast it into a 500 μm thick film. Dry and solidify it in a vacuum drying oven. Control the evaporation temperature to 40°C and the time to 18 hours to obtain a solid electrolyte membrane with uniform composition and a dual-phase structure.
[0060] The prepared solid electrolyte membrane was used to assemble an NCM811|solid electrolyte membrane|Li solid-state battery.
[0061] Performance Test:
[0062] (1) SEM analysis
[0063] The microstructure of the solid electrolyte membrane prepared in Example 3 was observed by scanning electron microscopy, and the following Figure 1 The solid electrolyte membrane having a dual-phase structure is shown, and Figure 2 A local magnified scanning electron microscope image of the two phases shown.
[0064] Figure 1 The dual-phase structure shown is alternately distributed throughout the solid electrolyte membrane, which gives the electrolyte membrane good mechanical stability; Figure 2 for Figure 1 A local magnified effect diagram of the two-phase structure. Figure 2 Phase A shown in (a) is a dispersed phase, presenting a honeycomb shape and rich in ion-conductive groups, which increases the surface area and mechanical strength of the electrolyte membrane. Figure 2 Phase B shown in (b) is the continuous phase and the main enriched area of PVDF-HFP polymer, which provides flexibility to the electrolyte membrane.
[0065] (2) Electrochemical impedance spectroscopy to measure ionic conductivity
[0066] The solid electrolyte membranes prepared in Examples 1-4 were subjected to electrochemical impedance tests and the following results were obtained: Figure 3 The impedance spectrum shown in the figure is tested under the following conditions: AMETEK1260A impedance / gain-phase analyzer, with the measurement voltage amplitude set to 5mV and the frequency set to 1HZ~1×10 6 HZ.
[0067] The impedance of Example 1 is 160.3Ω, and the ionic conductivity is 1.56×10 -3 S / cm; the impedance of Example 2 is 220.7Ω, and the ionic conductivity is 1.14×10 -3 S / cm; the impedance of Example 3 is 189.2Ω, and the ionic conductivity is 1.32×10 -3 S / cm; the impedance of Example 4 is 206.7Ω, and the ionic conductivity is 1.21×10 -3 S / cm. It can be seen that the ionic conductivity of the solid electrolyte membrane prepared by the present invention can reach 10 -3 The order of magnitude of S / cm shows a significant improvement in the electrochemical performance compared to conventional solid electrolyte membranes.
[0068] (3) Battery cycle performance
[0069] The NCM811|solid electrolyte membrane|Li solid-state battery assembled in Examples 1-4 was subjected to a cycle performance test and the following results were obtained: Figure 4 The cycle specific capacity curve is shown.
[0070] Among them, the battery of Example 1 has a capacity retention rate of more than 85% after 100 cycles at a rate of 1C; the battery of Example 2 can still be cycled relatively stably at a high rate of 2C, and although a capacity jump-type attenuation occurs around 80 cycles, there is still a capacity retention rate of 70% after 100 cycles; the battery of Example 3 is cycled 100 times at a rate of 2C, and the specific capacity curve is flat at a large rate, the battery stability is excellent, and there is no obvious capacity attenuation after the cycle; the battery of Example 4 is cycled 100 times at a rate of 0.5C, and the specific capacity curve is flat, the battery stability is good, and the capacity retention rate is close to 90%.
[0071] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a solid electrolyte membrane, characterized in that: The following steps are involved: Dissolve PVDF-HFP in an organic solvent, add lithium salt, and stir to prepare a polymer solution; Adding ceramic particles to the polymer solution, stirring and mixing to obtain a mixed solution in a reddish uniformly dispersed state; Adding deionized water to the mixed solution, stirring to obtain a phase-converted mixed solution; The mixed solution after the phase conversion is poured into a mold and dried and solidified into a film to obtain a solid electrolyte membrane; Wherein, the stirring is maintained at a temperature of 40-60°C.
2. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The average molecular weight of the PVDF-HFP is 350,000-455,000.
3. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The mass percentage of PVDF-HFP in the polymer solution is 9.9-15%; the mass percentage of lithium salt in the polymer solution is 0.1%-15%.
4. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The lithium salt is one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide or lithium perchlorate.
5. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The organic solvent is one of acetone, acetonitrile and tetrahydrofuran.
6. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The mass percentage of ceramic particles in the mixed solution is 15%-25%; the ceramic particles are any one of LLZTO, LLZO, LLTO or LATP.
7. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of the deionized water to the mixed solution is 1-2:
10.
8. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The temperature of the drying and curing film is 30-85°C.
9. A solid electrolyte membrane prepared according to the method according to any one of claims 1 to 8.
10. A lithium metal battery, characterized in that: Comprising the solid electrolyte membrane according to claim 9.